Children Death with Child Abuse: A Case Report at Bhayangkara Hospital, Kediri Indonesia - Mochammad Soekry Erfan Kusuma1 , Tutik Purwanti2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Child abuse has negative impact for children including emotional performance, mentaldysfunction, and decrease intelligence.Case report: A boy went to the emergency room at Bhayangkara Kediri Hospital. There was swelling on theleft head, expanding on the forehead and, bruising on the left ear. Also found signs of sodomy marks in theform of abrasions around the anus. There are also bruises on the back and neck of the end.Discussion: For a definitive diagnosis, the results of the CT scan were that the patient obtained extensivecerebral contusion and caused the deviation of the midline structure to the right as far as ± 0.9 cm withsubgaleal hematoma and the dilation of cerebral blood vessels.Conclusion: The body’s exact death is expected to blunt force in the head, resulting in a skull fracture andbleeding of the brain.